Pengaruh Kompetensi Terhadap Kinerja Pegawai DP3AP2KB Kota Cimahi Jawa Barat - Hendriyan, Arie; Sucipto, Bambang; Dzauharoh, Shinta (Universitas Batanghari Jambi, 2024)
Human resources are called the main capital for an organization, this is because HR can be a source of strength that comes from human potential to achieve goals. Among the organizational assets that must be maintained is human resources, especially when these human resources have good performance. The causes of employee performance are said to be good, one of which is competence. Employees who have good competence are able to complete tasks according to the targets set, because they have the desire to continue to improve their work results. The quality of human resources is determined by good management of human resource empowerment so as to form human resources who have a competitive spirit. Competence among employees is also important, and DP3AP2KB is no exception. The purpose of the research conducted was to find out the effect of competency on performance of employees at DP3AP2KB. The method in this study is quantitative explanatory research with a sample of 34 respondents with regression testing as a statistical analysis technique, determination, correlation, and hypothesis testing. From this study, it was found that there was a significant influence between competence on employee performance with a regression value Y = 9.674 + 0.855 X, and a coefficient of 0.930, in other words the level of strong relationship with a determination value of 86.5%. While the hypothesis test obtained a significance of 0.000 or less than 0.05.